Comparison of linear combination modeling strategies for edited magnetic resonance spectroscopy at 3 T. (23rd September 2021) - Zöllner, Helge J.; Tapper, Sofie; Hui, Steve C. N.; Barker, Peter B.; Edden, Richard A. E.; Oeltzschner, Georg
Abstract : J‐difference‐edited spectroscopy is a valuable approach for the in vivo detection of γ‐aminobutyric‐acid (GABA) with magnetic resonance spectroscopy (MRS). A recent expert consensus article recommends linear combination modeling (LCM) of edited MRS but does not give specific details regarding implementation. This study explores different modeling strategies to adapt LCM for GABA‐edited MRS. Sixty‐one medial parietal lobe GABA‐edited MEGA‐PRESS spectra from a recent 3‐T multisite study were modeled using 102 different strategies combining six different approaches to account for co‐edited macromolecules (MMs), three modeling ranges, three baseline knot spacings, and the use of basis sets with or without homocarnosine. The resulting GABA and GABA+ estimates (quantified relative to total creatine), the residuals at different ranges, standard deviations and coefficients of variation (CVs), and Akaike information criteria, were used to evaluate the models' performance. Significantly different GABA+ and GABA estimates were found when a well‐parameterized MM3co basis function was included in the model. The mean GABA estimates were significantly lower when modeling MM3co, while the CVs were similar. A sparser spline knot spacing led to lower variation in the GABA and GABA+ estimates, and a narrower modeling range—only including the signals of interest—did not substantially improve or degrade modeling performance. Additionally, the results suggest that LCM can separate GABA and the underlying co‐edited MM3co . Incorporating homocarnosine into the modeling did not significantly improve variance in GABA+ estimates. In conclusion, GABA‐edited MRS is most appropriately quantified by LCM with a well‐parameterized co‐edited MM3co basis function with a constraint to the nonoverlapped MM0.93, in combination with a sparse spline knot spacing (0.55 ppm) and a modeling range of 0.5–4 ppm. Abstract : One hundred and two strategies to model GABA‐edited MRS with linear combination modeling were evaluated to quantify GABA and GABA+ in Osprey. Significantly different GABA and GABA+ estimates were found when a well‐parameterized macromolecule at 3 ppm was included. The findings suggest that linear combination modeling needs to be adapted for quantification of GABA‐edited MRS.